Retraction Notice: Daily Consumption of Monosodium Glutamate Pronounced Hypertension and Altered Renal Excretory Function in Normotensive and Hypertensive Rats - Thongsepee, Nattaya; Martviset, Pongsakorn; Chantree, Pathanin; Sornchuer, Phornphan; Sangpairoj, Kant; Prathaphan, Parisa; Hiranyachattada, Siriphun (Asian Medical Journal and Alternative Medicine, 2022)
The article has been retracted at the request of the author.